"Learn to find inner peace:discover your true self manage your anxieties and emotions think well,feel well" - "George, Mike" (London, 2003)
It is easy to become vulnerable to stress and frustration in our daily lives. This book shows that by paying attention to our spirit we can attain greater clarity and depth of thinking, greater self-understanding, self-esteem and self-confidence, and greater peace of mind. At the same time, we can begin to enjoy life more. With the help of insights, meditative exercises and visualisations adapted from various traditions around the world, the author presents a wealth of ways for us to shake off the burden of the ego, clear the anxieties that cloud our perceptions, and break free to a higher plane of personal fulfilment. The book offers a blend of philosophical reflection, intuitive spiritual wisdom and practical self-development, conveyed through clear, down-to-earth advice.
Keywords: Spiritualism